Signal anomaly identification strategy based on Bayesian inference for nuclear power machinery. (December 2021) - You, Dongdong; Shen, Xiaocheng; Liu, Gaojun; Wang, Gaixia
Graphical abstract: Abstract: In the machinery industry, signal anomalies are generally identified using the threshold method, which exhibits shortcomings in setting reasonable thresholds, in decision-making when signals approach thresholds or fluctuate, and in quantification of fault confidence. In this paper, a long short-term memory (LSTM) model is established to predict the time-series signals. For prediction residual, a novel decision-making strategy of signal anomaly identification based on Bayesian inference is then proposed that considers data uncertainty. Various signal abnormality conditions are analyzed, and a Bayesian hypothesis test approach is developed to determine the signal status and quantify the fault probability. After fully mining the prior information of the residuals to reduce the influence of randomness, estimates of the key parameters, namely residual mean and variance, are determined by obtaining the posterior distribution based on the normal-inverse-gamma distribution. In two nuclear power machinery examples, all potential signal anomalies are identified by the proposed method. The results of a comparative analysis with existing methods demonstrate that the proposed method can issue an alarm several hours in advance and provide a fault probability, which improves the accuracy and reliability of prediction.